Acesso ao ensino superior no Ceará: a contribuição do Instituto Federal - Vieira, Magda Alves (2018)
Higher education has made significant advances in the last two decades, but it is still challenging to achieve the goal proposed by the National Education Plan. Some public policies were implemented with the objective of increasing access opportunities, among them the expansion of the Federal Network of Professional, Scientific and Technological Education. Several studies have already been carried out focusing on the growth of higher education in Brazil, but what is the state of the art regarding access in Ceará? How is access to this level considering the mesoregions of the State? What is the contribution of the Federal Institute in this process? Taking these questions as a starting point, this research seeks to analyze the contribution of the Federal Institute of Ceará in promoting access to higher education in the State. For the data collection were used the documentary analysis procedures, with secondary data collection, through the information available at the INEP and IBGE databases. The variables analyzed were: number of registrations, courses, educational institutions, areas, municipalities served, projection of population and GDP per capita, having as base year 2016. Data analysis shows that the predominance of enrollments is of the private administrative category, with 66.5% of the total. However, considering the mesoregions individually, the public offering is higher in 4 (four), among the 7 (seven): North, Northwest, South and Center-South. The Federal Institute of Ceará is present in 7 (seven) Mesoregions of the State with at least 2 (two) campuses with undergraduate courses in each. In the decade 2009-2018, it has graduated more than 3,700 professionals and has been contributing to reduce the deficit of higher education in interior State, being present in 23 municipalities, of the 31 that count on Institutions of Higher Education.